Religious Radicalism and Islamic Universities in Aceh: Between Campus, Environment and Family - Ismail, Sanusi; Abubakar, Bustami; Matsyah, Ajidar; Thalal, Muhammad; Yahya, Hermansyah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This paper discusses how Islam is understood, taught, and practiced at the State Islamic Religious Higher Education Institution (PTKIN) in Aceh, whether the contextual approach and tolerance towards difference approach are used, whether there is any indication of the development of religious radicalism, how PTKIN in Aceh positions itself towards this problem, and also, how the environment and family play their roles on this issue. This qualitative study collected data by means of observation, in-depth interview, documentation, and focus group discussion. The data were then analyzed in the following steps: data reduction, data display, verification, and conclusion drawing. The PTKIN selected as research sites consisted of Universitas Islam Negeri Ar-Raniry Banda Aceh, Institut Agama Islam Negeri Zawiyah Cot Kala Langsa, and Sekolah Tinggi Agama Islam Negeri Gajah Putih Takengon. In general, the findings revealed that PTKIN in Aceh has been relatively free from religious radicalism. The teaching of Islamic studies at PTKIN in Aceh still adheres to the Qur’an, Hadith and authoritative references from various sources and time periods, from classical to contemporary books, and from moderate to contextual approaches that respect differences in understanding. The small potential and threat of religious radicalism at PTKIN in Aceh, in addition to the academic system built within PTKIN itself, are influenced by the socio-cultural and political environment in Aceh which is quite accommodating to the aspirations of Islamic law. Islam in Aceh today is relatively compatible with the state because the state has given the Acehnese peoplethe right to exercise Islamic law, not only in the private sphere, but also in the public sphere. However, there is one potential threat that needs to be aware of, which is the way to commute between home and campus; and, this particular space needs to be bridged properly so that students will not be recruited by exclusive Islamic groups without the knowledge of the campus and their families.